(6x-2)/4=x-2

Simple and best practice solution for (6x-2)/4=x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6x-2)/4=x-2 equation:



(6x-2)/4=x-2
We move all terms to the left:
(6x-2)/4-(x-2)=0
We get rid of parentheses
(6x-2)/4-x+2=0
We multiply all the terms by the denominator
(6x-2)-x*4+2*4=0
We add all the numbers together, and all the variables
(6x-2)-x*4+8=0
Wy multiply elements
(6x-2)-4x+8=0
We get rid of parentheses
6x-4x-2+8=0
We add all the numbers together, and all the variables
2x+6=0
We move all terms containing x to the left, all other terms to the right
2x=-6
x=-6/2
x=-3

See similar equations:

| 200x+12=64 | | 8(s-3)=12 | | 4=t=3(t-1)=-5 | | x^2-5x+82=0 | | -4(8-5p)=8p+40 | | 3/x+12=0 | | 3(x+1)+4=19 | | 3/4x+1/2=4.5 | | 10=6x-20 | | 13-4x1=x | | 3(2x-5)-2x+3=1 | | 8z=9z-7 | | Y=-6x^2+108x-495 | | 3w=8w+110 | | 72°F=1.8x+32 | | -3-7a=1-5a | | Y=-6x^2+108x-486 | | 3/x+2=2/3x+13/6 | | 3(2x-13)+7x=65 | | 1/2(4-6x)+5=3 | | p-1/3=-4 | | 3x-3=7+5x | | 4(x+11)+5x=9x-44 | | -p-2=-10+7p | | 5(1=4m)=2(3+10m) | | 5(x-2)=3(x+4 | | 7x-138=x | | 125m-75m+38000=40800-150m | | 2x-5/8+x=2x+5/2+8 | | 2(6x+4)=6 | | 3+(1/4x)=56 | | (20+3g)+(20+2g)=115 |

Equations solver categories